COMPARATIVE EFFECT OF COMPOSITE FLOUR (MOCAF FLOUR, RICE FLOUR) AND THE ADDITION OF TELANG FLOWER EXTRACT (CLITORIA TERNATEA) AS A COLORING INGREDIENT AND SOURCE OF BIOACTIVE IN CUPCAKES - Hotman Manurung; Ferlando J. Simanungkalit; Demiana Welda Katrin (Jurnal Scientia, 2023)
Cupcakes on the market use rice flour which contains less fiber and use synthetic coloring. The aim of this research was to determine the effect of the ratio of rice flour to Mocaf and the effect of adding water extract of butterfly pea flower (Clitoria ternatea) on quality characteristics. Using a 2-factor Completely Randomized Factorial Design (RALF). Comparison of rice composite flour with mocaf (%): P0= 100:0; P1= 75:25; P2=50:50; P3= 25:75. Weight of butterfly pea flower K0= 0gr; K1=4gr; K2=8gr; K3=12gr and K4=16gr. The research was carried out with 3 replications. Parameters analyzed: Total Dissolved Solids (TPT), Weight gain of cupcakes, swelling ability of cupcakes and crude fiber content. The research data were analyzed using SPSS version 22 software. The mean difference test used the Duncan test at the level of p=0.05. Research result. Total dissolved solids increased from 9.05% to 13.28%. Cupcake weight gain increased from 30.5% to 66.8%. Expanding power increased from 52.6% to 82.29%. Crude fiber increased from 0.806% to 1.498%. Mocaf up to 75% can be used to substitute rice flour and butterfly pea flower weight up to 16g.